Effectiveness of a probiotic combination on the neurodevelopment of the very premature infant - Benjamin James Baucells; Giorgia Sebastiani; Leyre Herrero-Aizpurua; Vicente Andreu-Fernández; Elisabet Navarro-Tapia; Oscar García-Algar; Josep Figueras-Aloy (Scientific Reports, 2023)
Abstract Probiotics have shown a benefit in reducing necrotising enterocolitis in the premature infant, however the study of their effect on premature neonates’ neurodevelopment is limited. The aim of our study was to elucidate whether the effect of Bifidobacterium bifidum NCDO 2203 combined with Lactobacillus acidophilus NCDO 1748 could positively impact the neurodevelopment of the preterm neonates. Quasi-experimental comparative study with a combined treatment of probiotics in premature infants < 32 weeks and < 1500 g birth weight, cared for at a level III neonatal unit. The probiotic combination was administered orally to neonates surviving beyond 7 days of life, until 34 weeks postmenstrual age or discharge. Globally, neurodevelopment was evaluated at 24 months corrected age. A total of 233 neonates were recruited, 109 in the probiotic group and 124 in the non-probiotic group. In those neonates receiving probiotics, there was a significant reduction in neurodevelopment impairment at 2 years of age RR 0.30 [0.16–0.58], and a reduction in the degree of impairment (normal-mild vs moderate-severe, RR 0.22 [0.07–0.73]). Additionally, there was a significant reduction in late-onset sepsis (RR 0.45 [0.21–0.99]). The prophylactic use of this probiotic combination contributed to improving neurodevelopmental outcome and reduced sepsis in neonates born at < 32 weeks and < 1500 g.